Health and Social Care Bill 2011: a legal basis for charging and providing fewer health services to people in England. (8th March 2012) - Pollock, Allyson M; Price, David; Roderick, Peter
Abstract : Despite recent amendments to English health bill in response to opposition, Allyson Pollock, David Price, and Peter Roderick argue that it will enable charging for health services that are currently free